MULTIVARIATE STATISTICAL ANALYSIS OF WATER QUALITY OF WATER RESOURCES OF RISHIKESH BY USING WATER QUALITY INDEX TECHNIQUE (International Journal of Food and Nutritional Sciences, 2022)
Globally, the natural water quality of water resources is degrading due to human interference. To evaluate the water quality of a region, it is crucial to comprehend the interaction between human activities and its different uses for different purposes. In this study, an attempt has been made to give an index of water samples collected from the holy river Ganga at twenty-five sampling stations in the yoga city of Uttarakhand, India. The water samples collected from different monitoring locations were analysed for their physicochemical parameters like pH, turbidity, total hardness (TH), calcium (Ca2+), magnesium (Mg2+), total dissolved solids (TDS), electrical conductivity (EC), dissolved oxygen (DO), and biochemical oxygen demand (BOD), which specify the appropriateness of surface and sub-surface water for different domestic, commercial, agricultural, and industrial uses. This study reveals that the majority of the water samples were in the lower range of the alkalinity limit (pH 7.11–8.48). The range of the water quality index for the samples varied from 44.17 to 77.63. The higher values of WQI were seen due to the concentrations of nitrate, hardness, and sulphate in the water sample. According to the study's findings, many sites' Ganga River water can be used for residential and agricultural reasons; however, before consumption, safeguards and rigorous measures are required. The obtained results of this study may be extremely supportive to government officials, the general community, non-governmental organizations, shareholders, and policymakers in developing an appropriate water management strategy for society.